Deterrence and the Moral Context: Is the Impact of Perceived Sanction Risk Dependent on Best Friends’ Moral Beliefs? - Hirtenlehner, Helmut (Criminal justice review, 2021)
Research on differential deterrability suggests increasingly that the size of a potential sanction risk effect is conditional on characteristics of the person and properties of the setting. Whether the moral context of young people’s action settings shapes adolescents’ responsiveness to deterrent cues has been a neglected issue, however. Since youths spend much time in the company of their peers, close friends’ stance toward crime may serve as a measure of the moral makeup of the immediate environment in which young people make behavioral choices. Based on a longitudinal adolescent self-report survey, we test whether the impact of an individual’s sanction certainty perceptions varies according to the level of his or her best friends’ moral beliefs regarding selected acts of rule-breaking. Lagged negative binomial regression analyses provide mixed support for the hypothesis that perceived sanction risk matters more for adolescents whose close friends encourage criminal activity. These findings have wider implications for perceptual deterrence research: They suggest that efforts to specify the conditions under which sanction certainty perceptions are related to offending should concentrate on the presence of criminogenic factors.